Communities Putting Prevention to Work: Results of an Obesity Prevention Initiative in Child Care Facilities. Issue 3 (2nd July 2016) - Natale, Ruby; Camejo, Stephanie; Sanders, Lee M.
ABSTRACT: Obesity is a significant public health issue affecting even our youngest children. Given that a significant amount of young children are enrolled in child care, the goal of this project was to evaluate the effectiveness of a child care facility-based obesity prevention program. Over 1, 000 facilities participated in the study. The intervention consisted of teacher trainings and technical assistance focused around the implementation of four policies: snack, beverage, physical activity, and screen time. Changes in teacher's attitudes and beliefs, as well as improvements in healthy lifestyle practices, were assessed. Results revealed significant improvements in child care center practices, such as: (1) the amount of health-related lessons provided to students increased t(664) = −6.09, P  < 0.00; (2) the amount of outdoor physical activity increased t(702) = −3.83, P  < 0.000; (3) the amount of screen time decreased t(686) = −2.52, P  < 0.01; (4) the amount of juice served decreased t(577) = −7.38, P  < 0.000; and (5) the amount of junk food decreased t(568) = −2.73, P  < 0.006. The findings from this study can be easily disseminated and potentially serve as a model for improving the quality of nutrition and physical activity practices in child care facilities.